-4-5g=-4g+6

Simple and best practice solution for -4-5g=-4g+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-5g=-4g+6 equation:



-4-5g=-4g+6
We move all terms to the left:
-4-5g-(-4g+6)=0
We get rid of parentheses
-5g+4g-6-4=0
We add all the numbers together, and all the variables
-1g-10=0
We move all terms containing g to the left, all other terms to the right
-g=10
g=10/-1
g=-10

You can always share this solution

See similar equations:

| 6=8+(p)/(4) | | 6-7x=-2x+8-3 | | -8m+9=-6m-7 | | 14+x=5x | | 4n+9=-15 | | 110°+3x+11=16x+4 | | -1/3-g=1/3 | | -9f+5+1=9-10f | | p=p-11 | | -2w+10=2w-10 | | x3=-48 | | -10-2j=-4j+8+8j | | 3c+5=4c-1 | | 2(3k+5)=9k-3(k+4)-1 | | 5x+1+x-9=9x-80 | | -2-5b=-3b | | | | Y=3x-9x-27x | | 4x+34=1-6 | | Y=x2-225 | | 12x+3+7x-2=90 | | 7p/10+9=15 | | 2.5x=5x+3 | | 7r-15=2r+10 | | 11=7t/4 | | (2x-10)=-3 | | 50.50+4x=56.10 | | 3x-6=1x-18 | | 12-222x+34=180 | | 3+-1x=-4 | | (5-3n)=4 | | (2x)+58=180 |

Equations solver categories